2018
DOI: 10.1152/physrev.00029.2016
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoperones as Novel Therapeutics for Diverse Protein Conformational Diseases

Abstract: After synthesis, proteins are folded into their native conformations aided by molecular chaperones. Dysfunction in folding caused by genetic mutations in numerous genes causes protein conformational diseases. Membrane proteins are more prone to misfolding due to their more intricate folding than soluble proteins. Misfolded proteins are detected by the cellular quality control systems, especially in the endoplasmic reticulum, and proteins may be retained there for eventual degradation by the ubiquitin-proteasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 413 publications
(420 reference statements)
0
62
0
Order By: Relevance
“…It has been observed that PCs can increase the enzyme activity of the mutant proteins in a mutation-dependent manner, which may be sufficient to ameliorate most disease symptoms [49,50]. In addition, it has been observed that these drugs can enhance the stability of recombinant lysosomal enzymes, suggesting that co-administration of a PC and recombinant enzyme may increase the efficacy of the ERT [3,51]. Here, we will highlight some of the studies that have identified and characterized PCs for LSDs.…”
Section: Use Of Pharmacological Chaperones In Lsdsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that PCs can increase the enzyme activity of the mutant proteins in a mutation-dependent manner, which may be sufficient to ameliorate most disease symptoms [49,50]. In addition, it has been observed that these drugs can enhance the stability of recombinant lysosomal enzymes, suggesting that co-administration of a PC and recombinant enzyme may increase the efficacy of the ERT [3,51]. Here, we will highlight some of the studies that have identified and characterized PCs for LSDs.…”
Section: Use Of Pharmacological Chaperones In Lsdsmentioning
confidence: 99%
“…These proteins, also called molecular chaperones, act on proteins that reach the endoplasmic reticulum (ER) and on some cytosolic proteins, aiding in the proper folding of unfolded and misfolded proteins. In this sense, molecular chaperones reduce the amount of proteins that are targeted for degradation by decreasing their aggregation and proteasome targeting [3]. The ER environment is very different from that of the cytosol since it has an oxidizing nature that helps the disulfide bond formation and it also has a mM concentration of Ca 2+ , which acts as a folding buffer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological chaperones have ceased to be a niche category and have entered the clinical practice for some rare diseases caused primarily by protein instability. Many reviews exist to cover this subject with different points of view (a few examples [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]). We wanted to contribute by providing the readers with a list of research papers organized per disease that covers the years from 2000 to 2018.…”
Section: Introductionmentioning
confidence: 99%
“…For human diseases caused by proteostasis impairment, it is essential to identify or develop novel biological and chemical therapeutics aiming at optimizing protein conformation and enhancing proteostasis capacity (130,177,178). For example, the Hsp90 inhibitor 17-AAG may serve as a potential pharmacological chaperone (pharmacochaperone) for modifying impaired proteostasis network of neurodegenerative diseases such as motor neuron degeneration and spinocerebellar ataxia (131, 179,180).…”
Section: Clinical Significancementioning
confidence: 99%